2016
DOI: 10.1007/s10212-016-0296-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing problem-based learning students to students in a lecture-based curriculum: learning strategies and the relation with self-study time

Abstract: In educational theory, deep processing (i.e., connecting different study topics together) and self-regulation (i.e., taking control over one's own learning process) are considered effective learning strategies. These learning strategies can be influenced by the learning environment. Problem-based learning (PBL), a student-centered educational method, is believed to stimulate the use of these effective learning strategies. Several aspects of PBL such as discussions of real-life problems, selecting literature by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…Based on these factors, it can be concluded that most of the learning process is still teacher-centered it is inversely proportional to the characteristics of the problem-based learning models. The learning process in the PBL is more focused on the students as people learn (Wijnen et. Al., 2017).…”
Section: Secondary Datamentioning
confidence: 99%
“…Based on these factors, it can be concluded that most of the learning process is still teacher-centered it is inversely proportional to the characteristics of the problem-based learning models. The learning process in the PBL is more focused on the students as people learn (Wijnen et. Al., 2017).…”
Section: Secondary Datamentioning
confidence: 99%
“…Furthermore, he stated that the application of problem-based learning (PBL) is very useful in improving student performance in the classroom. They also found that through the application of PBL, students learn a new experience, namely real resolve issues close to the everyday lives of these students (Bahri, Putriana, & Idris, 2018), Students can analyze the problem and apply deductive and inductive processes to understand the problem and find a solution (Tarmizi & Bayat, 2010), PBL is also a significant learning model, practical and relevant in everyday problems of students (Albanese & Mitchell, 1993), Through the application of PBM, students feel the sensation of learning enjoyable, stimulating, and easily applied in solving real problems (De Vries, Schmidt, & de Graaff, 1989;Wijnen, Loyens, Smeets, Kroeze, & van der Molen, 2017),…”
Section: Figure 2 Interaction Between Students' Creative Thinking Abmentioning
confidence: 99%
“…The lecture format works because teachers are typically the primary transmitters of knowledge, while students are the knowledge receivers. However, although lecture-based instruction can be effective, it tends to create less engagement in learning [3][4][5].…”
Section: Introductionmentioning
confidence: 99%